Analysis of abstracts in English: A study of abstracts written by EFL writers in Argentina - Loutayf, Soledad (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
English is the preferred language in the international world of scholarship and research, but some EFL (English as a foreign language) scientists find linguistic barriers to interact confidently in this dialogue. Since genre and corpus studies have greatly contributed to the understanding and production of texts, I analysed a corpus of abstracts written by EFL writers in Salta, Argentina, to inform target writers and ESP (English for specific purposes) teachers about this genre which requires special attention. The aim of this article is to report findings on rhetorical structures and communicative purposes of the abstracts in this corpus to compare them with existing models in English literature, and to show the structures available that may help EFL science writers effectively improve their abstract writing skills and communicative purposes.